Teaching and placement of dental amalgam restorations at South African dental schools - Essa, Ameera Y.; Ahmed, Suwayda; Dyason, Achmat; Karjiker, Farzana; Adam, Razia Z. (Frontiers in Oral Health, 2023)
Introduction This paper set out to investigate the relationship between teaching and clinical practice of direct posterior restoration placement at tertiary dental institutions in South Africa. Methods A cross-sectional study using a mixed methods approach was conducted, and all the South African dental schools were invited to participate. The quantitative phase of the study analyzed the Conservative Dentistry department's records of direct restorations at a single dental school. The number of amalgam and tooth-colored restorations placed by students in the fourth and fifth year of the program from 2004 to 2019 were compared. During the qualitative phase, semi-structured interviews were held with staff from the four dental schools involved with the teaching of direct posterior restorations. Results The predominant direct posterior restoration placed in student clinics over a 15-year period at a South African dental school was tooth colored (75%). Teaching times do not correspond to a decrease in the placement of dental amalgam restorations for both one-surface and two-surface posterior restorations and a concomitant increase in the tooth-colored restorations. Discussion Academic staff involved in teaching identified that South Africa's ratification of the Minamata Convention has consequences for dental education and training. However, all schools reported that dental amalgam would continue to be taught in the absence of an appropriate alternative.